E40 glutenase detoxification capabilities of residual gluten immunogenic peptides in in vitro gastrointestinal digesta of food matrices made of soft and durum wheat - Mamone, Gianfranco; Comelli, Maria Cristina; Vitale, Serena; Di Stasio, Luigia; Kessler, Katharina; Mottola, Ilaria; Siano, Francesco; Cavaletti, Linda; Gianfrani, Carmen (Frontiers in Nutrition, 2022)
Gluten degrading enzymes, which are commonly referred to as ‘glutenases’, represent attractive candidates for the development of a pharmacological treatment of gluten related disorders, such as coeliac disease (CeD). Endoprotease-40 (E40), a novel glutenase secreted by the actinomycete Actinoallomurus A8 and recombinantly produced in S. lividans TK24, was shown to be active at pH 3 to 6 (optimum pH 5), resistant to pepsin and trypsin degradation, able to destroy immunotoxicity of the both gliadin 33-mer peptide and whole proteins and to strongly reduce the response of specific T cells when added to gliadin in in vitro gastrointestinal digestion. This study aims to functionally assess the capabilities of Endoprotease-40 (E40) to detoxify residual gluten immunogenic peptides in gastrointestinal digesta of food matrices made of soft and durum wheat. The Infogest harmonized protocols were applied to the multicompartmental model of simulated human gastrointestinal digestion, for the quantitative assessment of residual gluten in liquid (beer) and solid (bread and pasta) foods, made of either soft or durum wheat. Proteomic and immunological techniques, and functional assays on intestinal T cell lines from coeliac disease patients were used to identify gluten-derived immunogenic peptide sequences surviving in gastric and gastrointestinal digesta after the addition of E40 at increasing enzyme:wheat proteins ratios. During the gastric phase (2 h incubation time), the addition of E40 demonstrated an extensive (95%) dose-dependent detoxification of whole gluten in real food matrices. Overall, the residual gluten content was found at, or even below, the 20 ppm gluten-free threshold for soft and durum wheat-based food. Furthermore, unlike in untreated gastrointestinal digesta, none of the immunodominant α-gliadin peptides survived in E40-treated digesta. Traces of - and -gliadin derived immunogenic peptides were still detected in E40-treated digesta, but unable to stimulate celiac-intestinal T cells. In conclusion, E40 is a promising candidate for the oral enzymatic therapy of CeD, as a stand-alone enzyme being efficient along the complete gastrointestinal digestion of gluten.